Desenvolvimento de métodos de preparo de amostras para a determinação de impurezas elementares em medicamentos de uso oral - Cauduro, Vitoria Hagemann (2019)
In this study, sample preparation methods were developed for the digestion of oral pharmaceutical drugs used in the treatment of type 2 diabetes, with the objective of quantifying elemental impurities from classes 1 (As, Cd, Hg and Pb) and 2A (Co, Ni and V) by inductively coupled plasma optical emission spectrometry (ICP-OES). For this, the microwave induced combustion (MIC), microwave-assisted wet digestion (MAWD) and microwave and ultraviolet-assisted wet digestion (MAWD-UV) methods were evaluated. Six pharmaceutical drugs from different classes, containing metformine hydrochloride (MET), glibenclamide (GLIB), pioglitazone hydrochloride (PIO), sitagliptin hydrochloride (SITA), canagliflozin (CANA) and repaglinide (REPA) were used for the development of the methods. The drugs MET and CANA were chosen for the optimization of the methods. For the MIC method, the reflux step (5 or 10 min), the absorbing solution (7 and 14.4 mol L-1 HNO3, mixtures of 14.4 mol L-1 HNO3, 12 mol L-1 HCl and H2O in the proportion of 1+1+1, and mixtures of 14.4 mol L-1 HNO3 and 12 mol L-1 HCl in the proportions of 1+1, 1+3 and 3+1), and the use of combustion aids (microcrystallin cellulose or NH4Cl) were evaluated. For the MAWD method, the irradiation time (45 or 55 min), the digestion solution (1, 2, 3, 7 or 14.4 mol L-1 HNO3), the addition of an auxiliary reagent (1 or 2 mL of 50% H2O2) and the use of simultaneous cooling during the digestion (60 m3 h-1 or 125 m3 h-1 air flow rate) were evaluated. As for the MAWD-UV method, the following conditions were used: 1 mol L-1 HNO3, irradiation program of 55 min with simultaneous cooling (air flow rate of 125 m3 h-1 ), with the auxiliary reagent being evaluated (1.6 or 3.2 mL of 50% H2O2). For all the procedures, both the carbon concentration and residual acidity were determined in the digests. The accuracy of the methods was evaluated based on analyte recovery after standard addition assays and, for the MAWD and MAWD-UV methods, by the digestion of certified reference materials (CRM). When using MIC, V recoveries were not possible for samples containing inorganic excipients. For the MAWD method, CANA digestion was possible using 3 mol L-1 HNO3, 1 mL of 50% H2O2 and a 55 min irradiation program. The digestion of the other samples was possible using 2 mol L-1 HNO3, 1 mL of 50% H2O2 and a 45 min irradiation program. By using MAWD-UV, it was possible to digest all samples using 1 mol L-1 HNO3, 1.6 mL of 50% H2O2 and a 55 min irradiation program. The resulting digests from the optimized methods contained low residual acidity and dissolved carbon, enabling the analytes’ determination free of interferences by ICP-OES. In this way, it was possible to develop efficient methods for the decomposition of oral pharmaceutical drugs and subsequent class 1 and 2A (ICH Q3D guidelines) elemental impurities determination.